Consolidating Observation of Land and Sea Level Changes around South Georgia Island - TEFERLE, Felix Norman; HUNEGNAW, Addisu; Hibbert, Angela; Williams, Simon; Woodworth, Phil; Dalziel, Ian; Smalley, Robert Jr.; Lawver, Laurence (2019)
With its mid-ocean location in the Southern Atlantic Ocean South Georgia Island is in a key position for the oceanic and geodetic global monitoring networks. Since 2013 the tide gauge at King Edward Point (KEP) with GLOSS ID 187 has been monitored using a GNSS station nearby on Brown Mountain. By accurately geo-referencing the tide gauge and monitoring any vertical land movements, a continuous record of its datum within the Permanent Service for Mean Sea Level (PSMSL) can be established, which in turn makes the recorded and averaged sea levels useful for long-term studies and satellite altimetry calibrations. In 2014 another GNSS station was installed at KEP after local subsidence was sus-pected and later on three additional GNSS stations came to service at the periphery of the main island, making it possible to monitor uplift/subsidence wider afield. Further-more, together with four precise levelling campaigns of the KEP benchmark network in 2013, 2014 and two in 2017, it has also been possible to investigate the very local character of the vertical motions near KEP, i.e. the stability of the jetty upon which the tide gauge is mounted. In this study, we will present the results from the GNSS and precise levelling meas-urements, and will discuss their impact on the sea level record from the KEP tide gauge and nearby satellite altimetry sea surface heights. This study comes at a timely manner as during the Austral Summer 2019/2020 the jetty will be stabilized and en-larged, and consequently the current tide gauge will be replaced by a new one. Our measurements show that uplift is observed all over South Georgia Island while the ar-ea at KEP and particularly the jetty with tide gauge are subsiding relative to the rest of the island. In contrast, results for the tide gauge record show a lower magnitude of ob-served sea level rise than expected from nearby satellite altimetry. We will revisit all geodetic and oceanic observations in an attempt to improve the agreement between these measurements to summarize the ...